Hybrid algorithms for 3-SAT optimisation using MapReduce on clouds. (2018) - Barreto, Marcos; Nesmachnow, Sergio; Tchernykh, Andrei
This article presents the advances on applying a MapReduce approach for solving optimisation problems using Hadoop on cloud computing systems. The main advantages and limitations of the proposed strategy are presented and commented. A concrete case study is reported, analysing several algorithmic approaches to solve the 3-SAT, a well-known version of the Boolean satisfiability problem. Several variants of the MapReduce 3-SAT solver are designed and evaluated to demonstrate that the collaborative approach is a promising option for solving optimisation problems in the cloud.